Allopolyploidy has a moderate impact on restructuring at three contrasting transposable element insertion sites in resynthesized Brassica napus allotetraploids. Issue 2 (6th February 2013) - Sarilar, Véronique; Palacios, Paulina Martinez; Rousselet, Agnès; Ridel, Céline; Falque, Matthieu; Eber, Frédérique; Chèvre, Anne‐Marie; Joets, Johann; Brabant, Philippe; Alix, Karine
Summary: The role played by whole‐genome duplication (WGD) in evolution and adaptation is particularly well illustrated in allopolyploids, where WGD is concomitant with interspecific hybridization. This 'Genome Shock', usually accompanied by structural and functional modifications, has been associated with the activation of transposable elements (TEs). However, the impact of allopolyploidy on TEs has been studied in only a few polyploid species, and not in Brassica, which has been marked by recurrent polyploidy events. Here, we developed sequence‐specific amplification polymorphism (SSAP) markers for three contrasting TEs, and compared profiles between resynthesized Brassica napus allotetraploids and their diploid Brassica progenitors. To evaluate restructuring at TE insertion sites, we scored changes in SSAP profiles and analysed a large set of differentially amplified SSAP bands. No massive structural changes associated with the three TEs surveyed were detected. However, several transposition events, specific to the youngest TE originating from the B. oleracea genome, were identified. Our study supports the hypothesis that TE responses to allopolyploidy are highly specific. The changes observed in SSAP profiles lead us to hypothesize that they may partly result from changes in DNA methylation, questioning the role of epigenetics during the formation of a new allopolyploid genome.